A Study of Problematic Areas of English Collocations at Higher Secondary Level in Pakistani ESL Learners - Ghani, Nadia Abdul; Hafeez, Muhammad Rashid (Pakistan Languages and Humanities Review, 2025)
Collocations are a significant challenge in Pakistani L2 acquisition due to grammar focus, and limited lexical knowledge. The objectives of this descriptive quantitative study were to find out the problematic areas of English lexical Collocations among the Pakistani students of Higher Secondary level. This study investigated the role of the mother tongue in lexical collocations errors and the role of Collocations in second language learning with the framework of Benson, Benson, and Illson (1997). The data was collected through a multiple-choice questionnaire of English collocations with 600 randomly sampled (300 male/300 female) students of 6 Lahore government colleges. Findings showed that Collocations are problematic (Adj+N, 62.4%, V+N, 58.2%, Adv+Adj, 43.64%, N+N, 40.9%) due to interference of mother language and limited knowledge. This study suggests the solution as early material introduction, comprehensive collocation knowledge with updated teaching methods. Other researchers can include teachers’ survey with different educational levels and approaches.